THE USE OF WORDLIST PLUS PICTURE TO INCREASE STUDENTS’ STOCK OF VOCABULARY - Christin I. M. Pangaila; Meity Muntuuntu; Paula Rombepajung (KOMPETENSI, 2021)
This research aimed to see the effectiveness of using Wordlist plus picture in increasing students’ stock of vocabulary at the seventh grade of SMP Negeri 2 Tenga. This research used pre- experimental designed with one group pre-test and post-test. The result of this research found that Wordlist plus picture was effective in increasing students’ stock of vocabulary. The result showed that post-test was higher than pre-test. The mean score of pre-test was 5.00 and the mean score of post-test is 7.25 which means that the result of the post-test is higher than the pre-test. It can be stated that the students’ stock of vocabulary at the seventh grade of SMP N 2 Tenga is high in the post-test. So, it means Wordlist plus picture is effective in increasing students’ stock ofvocabulary at the seventh grade of SMP N 2 Tenga.